A porous ion-conducting membrane, its preparation method and application

CN122659209BActive Publication Date: 2026-10-16HANGZHOU DEHAI AIKE ENERGY TECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202611160208.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-08-03
Publication Date
2026-10-16
Estimated Expiration
2046-08-03

AI Technical Summary

Technical Problem

但通过非溶剂相转化法制备的PVDF多孔离子传导膜,由于其具备多孔的特性,以及基材的强疏水性等的限制,难以获得高阻钒性和高离子传导性,使得电池库仑效率、电压效率以及容量保持等性能较差

Benefits of technology

1、本发明多孔离子传导膜在制膜过程中,在PVDF制膜液中添加溶剂染料,溶剂染料完全溶解于PVDF制膜液溶剂中,可使溶剂染料分子均匀分布在PVDF多孔离子传导膜基质形成的孔道表面,由于溶剂染料分子中具备含氮基团,在强酸性电解液中可质子化,可阻碍钒离子的通过,有效提升膜的阻钒性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122659209B_ABST
    Figure CN122659209B_ABST
Patent Text Reader

Abstract

The present application relates to vanadium flow battery diaphragm technical field, especially to a kind of porous ion conducting membrane and its preparation method and application.It includes PVDF powder, solvent dye, organic pigment, organic solvent mixing stirring heating dissolution preparation membrane preparation liquid, membrane preparation liquid is scraped on glass plate, impregnates pure water coagulation bath and prepares porous ion conducting membrane, after treatment, the porous ion conducting membrane is microwave heated, and post-processing porous ion conducting membrane is prepared.The present application is prepared porous ion conducting membrane by PVDF and solvent dye containing nitrogen group, organic pigment particle containing nitrogen group and having specific particle size are mixed, the pore structure is optimized, the inside and outside hole surface properties of membrane are improved, so that the membrane has color, thereby enhancing the membrane resistance vanadium, ion conductivity, modified performance stability, and the monitoring of film modification uniformity is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of vanadium redox flow batteries, and more particularly to a porous ion-conducting membrane, its preparation method, and its application. Background Technology

[0002] Vanadium redox flow batteries (VFBs) are a novel type of energy storage device with broad application prospects in photovoltaic power generation, wind power generation, emergency power supplies, and grid peak shaving and valley filling. The ion-conducting membrane is one of the key components of a VFB. Generally, the ion-conducting membrane is required to have high vanadium resistance and high ion conductivity, while the substrate used in the membrane should also possess high chemical stability and low cost. Currently, the membrane material used domestically and internationally is mainly perfluorosulfonic acid (PFSA) membrane. PFSA membranes exhibit excellent performance in terms of electrochemical properties and lifespan, but they are expensive and suffer from poor ion selectivity in VFBs, thus limiting their application. Therefore, developing battery membrane materials with high selectivity, high stability, and low cost is crucial.

[0003] Porous ion conducting membranes (POMs) achieve isolation of positive and negative electrode active materials and conduction of charge carriers by controlling their pore structure, including pore size, pore size distribution, and pore connectivity. Polyvinylidene fluoride (PVDF) is used as the substrate to prepare porous ion conducting membranes via a solvent-free phase inversion method. These membranes possess advantages such as high mechanical strength, good chemical stability, and low cost, making them highly valuable for applications in vanadium redox flow batteries. However, due to their porous nature and the strong hydrophobicity of the substrate, PVDF porous ion conducting membranes prepared via the solvent-free phase inversion method are limited in achieving high vanadium resistance and high ion conductivity, resulting in poor battery coulombic efficiency, voltage efficiency, and capacity retention. In existing modification preparation methods, most of them improve the vanadium blocking and ion conductivity of porous ion conduction membranes by surface treatment and internal pore filling with highly hydrophilic materials. However, these hydrophilic modified materials are unstable in the strong acid and strong redox system of vanadium redox batteries and are easily lost, resulting in performance degradation after multiple charge-discharge cycles. At the same time, the uniformity of the modified membrane is difficult to monitor. Summary of the Invention

[0004] To address the aforementioned issues, this invention combines PVDF with solvent dyes and organic pigments in a specific ratio to enhance the vanadium barrier properties, ion conductivity, and stability of the membrane, while also enabling monitoring of the modification uniformity. The solubility of the solvent dyes and the protonation of nitrogen-containing groups ensure uniform distribution of dye molecules on the inner and outer pore surfaces of the PVDF porous ion-conducting membrane, thereby improving the membrane's vanadium barrier properties. The interstitial spaces, insolubility, and protonation of nitrogen-containing groups on the surface of the organic pigment particles optimize the pore structure, ion conductivity, and vanadium barrier properties of the PVDF porous ion-conducting membrane. The hydrophobicity, resistance to strong acids and oxidation, and insolubility in electrolytes of the solvent dyes and organic pigments enhance the stability of the membrane performance. The color and color intensity distribution of the solvent dyes and organic pigments themselves allow for monitoring of the membrane modification uniformity. This results in a high-performance PVDF porous ion-conducting membrane.

[0005] To achieve the above objectives, the technical solution adopted by the present invention is as follows: In the first aspect, a method for preparing a porous ion-conducting membrane is disclosed, which specifically includes the following steps: Step S1: Mix PVDF powder, solvent dye, organic pigment and organic solvent, heat and stir to dissolve, cool and degas under vacuum to obtain film-forming solution; wherein, the solvent dye and the organic pigment both contain nitrogen-containing groups; Step S2: The film-forming solution is coated onto the substrate and immersed in a pure water non-solvent coagulation bath for phase transformation. After removal, it is subjected to microwave heating treatment and then soaked and washed in deionized water to obtain a porous ion-conducting membrane.

[0006] In one implementation, in step S1: The mass ratio of the PVDF powder, the solvent dye, the organic pigment and the organic solvent is (15~25):(1~5):(1~5):(65~83).

[0007] In one implementation, in step S1: The solvent dye is any one of Solvent Yellow 16, Solvent Yellow 33, Solvent Blue 63, and Solvent Blue 122; The organic solvent is any one of N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide, and N-methylpyrrolidone.

[0008] In one implementation, in step S1: The organic pigment is in granular form with a particle size of 0.5~2μm; The organic pigment is any one of Pigment Yellow 139, Pigment Yellow 63, Pigment Orange 16, and Pigment Orange 34.

[0009] In one implementation, in step S1: The heating and stirring dissolution process is carried out at a temperature of 70°C, a rotation speed of 500~1000 r / min, and a time of 2~5 h. The vacuum degassing time is 24 hours; The film-forming solution is stored at room temperature and in an environment with an air humidity of RH < 40%.

[0010] In one implementation, in step S2: The thickness of the coating is 200~300μm; The temperature of the pure water non-solvent coagulation bath is 20~30℃; The settling time for the phase transformation is 5 to 20 minutes.

[0011] In one implementation, in step S2: The microwave heating treatment time is 20~40s; The soaking and cleaning time is 60-120 minutes.

[0012] Secondly, a porous ion-conducting membrane is disclosed, which is prepared by the preparation method described above.

[0013] In one embodiment, the porous ion-conducting membrane contains solvent dyes and organic pigments, and the uniformity of membrane modification is monitored by the chromophores contained in the solvent dyes and organic pigments.

[0014] Thirdly, an application of a porous ion-conducting membrane is disclosed. The porous ion-conducting membrane prepared by the above-described method, or the porous ion-conducting membrane described above, is applied to an all-vanadium redox flow battery, wherein... The porous ion-conducting membrane has a coulombic efficiency of no less than 99.22% in the vanadium redox flow battery. The porous ion-conducting membrane has an energy efficiency of no less than 85.47% in the vanadium redox flow battery. The porous ion-conducting membrane retains no less than 99.46% of its capacity in the vanadium redox flow battery. The porous ion-conducting membrane achieves a coulombic efficiency of no less than 99.24% after 500 cycles in the vanadium redox flow battery. The porous ion-conducting membrane has an energy efficiency of no less than 85.08% after 500 cycles in the vanadium redox flow battery. The porous ion-conducting membrane retains no less than 94.32% of its capacity after 500 cycles in the vanadium redox flow battery.

[0015] The beneficial effects of this invention are: 1. In the process of forming the porous ion-conducting membrane of the present invention, a solvent dye is added to the PVDF forming solution. The solvent dye is completely dissolved in the PVDF forming solution solvent, which allows the solvent dye molecules to be uniformly distributed on the pore surface formed by the PVDF porous ion-conducting membrane matrix. Since the solvent dye molecules have nitrogen-containing groups, they can be protonated in a strongly acidic electrolyte, which can hinder the passage of vanadium ions and effectively improve the vanadium barrier properties of the membrane.

[0016] 2. In the process of forming the porous ion-conducting membrane of the present invention, organic pigments are added to the PVDF film-forming solution. Micro- and nano-sized organic pigment particles are dispersed in the film-forming solution. During the non-solvent phase transformation process, due to the gaps between the pigment particles and the incompatibility with the PVDF porous membrane substrate, the porous membrane has more micropores, forming ion transport channels and effectively improving the ion conductivity of the membrane. At the same time, the surface of the organic pigment particles has nitrogen-containing groups, which can further enhance the vanadium barrier properties of the membrane.

[0017] 3. In the membrane fabrication process of the porous ion-conducting membrane of the present invention, solvent dyes and organic pigments are used as modifiers. Due to their strong hydrophobicity, they are insoluble in electrolytes and not easily lost. They also have certain resistance to strong acids and strong oxidation, and can exist stably in the membrane, effectively improving the stability of the modified properties.

[0018] 4. In the process of fabricating the porous ion-conducting membrane of the present invention, solvent dyes and organic pigments are used as modifiers. Since the molecules have chromophores, the porous membrane can be colored. The uniformity of membrane modification can be monitored by the depth and distribution of the membrane color. Attached Figure Description

[0019] Figure 1 This is a schematic flowchart of the preparation method of the porous ion-conducting membrane of the present invention.

[0020] Figure 2 The images show actual photos of the porous ion-conducting membranes of Comparative Example 1 and Example 1 of the present invention. Detailed Implementation

[0021] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to the accompanying drawings and embodiments. However, it should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the scope of the invention. Furthermore, descriptions of well-known structures and technologies are omitted in the following description to avoid unnecessarily obscuring the concept of the invention.

[0022] See Figure 1 A method for preparing a porous ion-conducting membrane, specifically including the following steps: Step S1: Take PVDF powder, solvent dye, organic pigment, and organic solvent, stir at high speed at 500~1000 r / min, heat at 70℃ for 2~5 h to dissolve, cool, and then degas under vacuum for 24 h to obtain the film-forming solution; the mass ratio of the PVDF powder, solvent dye, organic pigment, and organic solvent is (15~25):(1~5):(1~5):(65~83). The solvent dye is any one of Solvent Yellow 16, Solvent Yellow 33, Solvent Blue 63, and Solvent Blue 122; the organic solvent is any one of N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide, and N-methylpyrrolidone. The organic pigment is granular with a particle size of 0.5~2μm; the organic pigment is any one of Pigment Yellow 139, Pigment Yellow 63, Pigment Orange 16, and Pigment Orange 34; the film-forming solution is stored at room temperature and in an environment with an air humidity RH < 40%.

[0023] Step S2: Using a coating blade, the film-forming solution is coated onto a clean glass plate. The glass plate coated with the solution is then uniformly immersed in a pure water non-solvent coagulation bath at 20-30°C. It is then pressed firmly with a stainless steel frame and allowed to stand for 5-20 minutes. After this, the membrane is removed from the glass plate and subjected to microwave heating for 20-40 seconds. Finally, it is soaked and washed in deionized water for 60-120 minutes to obtain a porous ion-conducting membrane. The coating thickness is 200-300 μm.

[0024] Example 1: The following technical solution is adopted. Step S1: 15 parts by weight of PVDF powder, 1 part by weight of Solvent Yellow 16, 1 part by weight of Pigment Yellow 139 with a particle size of 0.5 μm and 65 parts by weight of N,N-dimethylformamide were dissolved by high-speed stirring and heating at 70°C for 2 hours at a stirring speed of 500 r / min. After cooling, the mixture was degassed under vacuum for 24 hours to obtain the film-forming solution, which was then stored at room temperature and in an environment with an air humidity of RH < 40% for later use. Step S2: Use a coating blade to coat the film-forming solution onto a clean glass plate to a thickness of 200 μm. Immerse the glass plate coated with the film-forming solution into a 20°C pure water non-solvent coagulation bath at a uniform speed, press it firmly with a stainless steel frame, let it stand for 5 minutes, peel the membrane off the glass plate, microwave heat treatment for 20 seconds, and then soak and wash it in deionized water for 60 minutes to obtain a porous ion-conducting membrane.

[0025] Example 2: The following technical solution is adopted. Step S1: Dissolve 18 parts by weight of PVDF powder, 2 parts by weight of Solvent Yellow 33, 2 parts by weight of Pigment Yellow 63 with a particle size of 1 μm and 70 parts by weight of N,N-dimethylacetamide by high-speed stirring and heating at 70°C for 3 hours at a stirring speed of 650 r / min. After cooling, degas under vacuum for 24 hours to obtain the film-forming solution, and store it at room temperature and with an air humidity of RH < 40% for later use. Step S2: Use a coating blade to coat the film-forming solution onto a clean glass plate to a thickness of 230 μm. Immerse the glass plate coated with the film-forming solution into a 23°C pure water non-solvent coagulation bath at a uniform speed, press it firmly with a stainless steel frame, let it stand for 10 minutes, peel the membrane off the glass plate, microwave heat treatment for 27 seconds, and then soak and wash it in deionized water for 80 minutes to obtain a porous ion-conducting membrane.

[0026] Example 3: The following technical solution is adopted. Step S1: Dissolve 22 parts by weight of PVDF powder, 4 parts by weight of Solvent Blue 63, 4 parts by weight of Pigment Orange 16 with a particle size of 1.5 μm and 77 parts by weight of dimethyl sulfoxide by high-speed stirring and heating at 70°C for 4 hours at a stirring speed of 850 r / min. After cooling, degas under vacuum for 24 hours to obtain the film-forming solution, and store it at room temperature and in an environment with an air humidity of RH < 40% for later use. Step S2: Use a coating blade to coat the film-forming solution onto a clean glass plate to a thickness of 270 μm. Immerse the glass plate coated with the film-forming solution into a 27°C pure water non-solvent coagulation bath at a uniform speed, press it firmly with a stainless steel frame, let it stand for 15 minutes, peel the membrane off the glass plate, microwave heat treatment for 33 seconds, and then soak and wash it in deionized water for 100 minutes to obtain a porous ion-conducting membrane.

[0027] Example 4: The following technical solution is adopted. Step S1: Dissolve 25 parts by weight of PVDF powder, 5 parts by weight of Solvent Blue 122, 5 parts by weight of Pigment Orange 34 with a particle size of 2 μm and 83 parts by weight of N-methylpyrrolidone by high-speed stirring and heating at 70°C for 5 h at a stirring speed of 1000 r / min. After cooling, degas under vacuum for 24 h to obtain the film-forming solution, and store it at room temperature and with an air humidity of RH < 40% for later use. Step S2: Use a coating blade to coat the film-forming solution onto a clean glass plate to a thickness of 300 μm. Immerse the glass plate coated with the film-forming solution into a 30°C pure water non-solvent coagulation bath at a uniform speed, press it firmly with a stainless steel frame, let it stand for 20 minutes, peel the membrane off the glass plate, microwave heat treatment for 40 seconds, and then soak and wash it in deionized water for 120 minutes to obtain a porous ion-conducting membrane.

[0028] Comparative Example 1: The following technical solution is adopted. Step S1: Dissolve 15 parts by weight of PVDF powder and 65 parts by weight of N,N-dimethylformamide by high-speed stirring and heating at 70°C for 2 hours at a stirring speed of 500 r / min. After cooling, degas under vacuum for 24 hours to obtain the film-forming solution, and store it at room temperature and air humidity RH<40% for later use. Step S2: Use a coating blade to coat the film-forming solution onto a clean glass plate to a thickness of 200 μm. Immerse the glass plate coated with the film-forming solution into a 20°C pure water non-solvent coagulation bath at a uniform speed, press it firmly with a stainless steel frame, let it stand for 5 minutes, peel the membrane off the glass plate, microwave heat treatment for 20 seconds, and then soak and wash it in deionized water for 60 minutes to obtain a porous ion-conducting membrane.

[0029] Comparative Example 2: The following technical solution is adopted. Step S1: Dissolve 15 parts by weight of PVDF powder, 1 part by weight of Solvent Yellow 16 and 65 parts by weight of N,N-dimethylformamide by high-speed stirring and heating at 70°C for 2 hours at a stirring speed of 500 r / min. After cooling, degas under vacuum for 24 hours to obtain the film-forming solution, and store it at room temperature and air humidity RH<40% for later use. Step S2: Use a coating blade to coat the film-forming solution onto a clean glass plate to a thickness of 200 μm. Immerse the glass plate coated with the film-forming solution into a 20°C pure water non-solvent coagulation bath at a uniform speed, press it firmly with a stainless steel frame, let it stand for 5 minutes, peel the membrane off the glass plate, microwave heat treatment for 20 seconds, and then soak and wash it in deionized water for 60 minutes to obtain a porous ion-conducting membrane.

[0030] Comparative Example 3: The following technical solution is adopted. Step S1: Dissolve 15 parts by weight of PVDF powder, 1 part by weight of Pigment Yellow 139 with a particle size of 0.5 μm and 65 parts by weight of N,N-dimethylformamide by high-speed stirring and heating at 70°C for 2 hours at a stirring speed of 500 r / min. After cooling, degas under vacuum for 24 hours to obtain the film-forming solution, and store it at room temperature and in an environment with an air humidity of RH < 40% for later use. Step S2: Use a coating blade to coat the film-forming solution onto a clean glass plate to a thickness of 200 μm. Immerse the glass plate coated with the film-forming solution into a 20°C pure water non-solvent coagulation bath at a uniform speed, press it firmly with a stainless steel frame, let it stand for 5 minutes, peel the membrane off the glass plate, microwave heat treatment for 20 seconds, and then soak and wash it in deionized water for 60 minutes to obtain a porous ion-conducting membrane.

[0031] Experimental Procedure and Data: The porous ion-conducting membranes prepared in the examples and comparative examples were respectively assembled into fuel cells and subjected to charge-discharge tests under the same test conditions. The test charge-discharge current density was 100 mA / cm².2 The battery coulombic efficiency, voltage efficiency, energy efficiency, and capacity retention were recorded. Data from the 10th and 500th cycles were used, and the test data are shown in Table 1.

[0032] Table 1. Test results of coulombic efficiency, voltage efficiency, energy efficiency, and capacity retention of porous ion-conducting membranes.

[0033] As shown in Table 1, Comparative Example 1, which prepared a porous PVDF ion-conducting membrane via a non-solvent phase inversion, suffered from limitations in its preparation method and the strong hydrophobicity of the substrate, making it difficult to achieve high vanadium barrier properties and high ion conductivity. Consequently, the coulombic efficiency and voltage efficiency in charge-discharge tests were low, resulting in a low overall energy efficiency. In Comparative Example 2, compared to Comparative Example 1, a solvent dye was added to the PVDF film-forming solution. The solvent dye was completely dissolved in the PVDF film-forming solution solvent, allowing the solvent dye molecules to be uniformly distributed on the pore surface of the PVDF porous ion-conducting membrane matrix. Because the solvent dye molecules contain nitrogen-containing groups, they can be protonated in a strongly acidic electrolyte, hindering the passage of vanadium ions and effectively improving the vanadium barrier properties of the membrane. Therefore, the coulombic efficiency in charge-discharge tests was significantly improved. Compared to Comparative Example 1, Comparative Example 3 added organic pigments to the PVDF film-forming solution. The micro- and nano-sized organic pigment particles dispersed in the solution, during the non-solvent phase transition, due to the gaps between the pigment particles and their incompatibility with the PVDF porous membrane substrate, the porous membrane possesses more micropores, forming ion transport channels and effectively improving the membrane's ion conductivity. Simultaneously, the nitrogen-containing groups on the surface of the organic pigment particles further enhance the membrane's vanadium barrier properties, thus significantly improving the coulombic efficiency and voltage efficiency in charge-discharge tests. Examples 1-4, compared to Comparative Example 1, combined the beneficial effects of Comparative Examples 2-3, resulting in significantly improved coulombic efficiency and voltage efficiency in charge-discharge tests. Furthermore, in Examples 1-4, solvent dyes and organic pigments were used as modifiers. Due to their strong hydrophobicity, insolubility in the electrolyte, and resistance to strong acids and oxidation, they can stably exist within the membrane, effectively improving the stability of the modified properties. Therefore, high coulombic efficiency and capacity retention were maintained even after 500 charge-discharge cycles. Figure 2 The images show the physical images of the porous ion-conducting membranes of Comparative Example 1 and Example 1. It can be seen that the PVDF porous ion-conducting membrane prepared in Comparative Example 1 is uniformly white and semi-transparent, while the membrane prepared in Example 1 is yellow. Therefore, solvent dyes and organic pigments are used as modifiers. Since the molecules have chromophores, the porous ion-conducting membranes can be colored. The uniformity of membrane modification can be monitored by the depth and distribution of the membrane color.

[0034] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. A method for preparing a porous ion-conducting membrane, characterized in that, Specifically, the steps include the following: Step S1: Mix PVDF powder, solvent dye, organic pigment, and organic solvent, heat and stir to dissolve, cool and degas under vacuum to obtain a film-forming solution; wherein the solvent dye and the organic pigment both contain nitrogen-containing groups; the solvent dye is any one of Solvent Yellow 16, Solvent Yellow 33, Solvent Blue 63, and Solvent Blue 122; the organic pigment is any one of Pigment Yellow 139, Pigment Yellow 63, Pigment Orange 16, and Pigment Orange 34; Step S2: The film-forming solution is scraped onto the substrate, immersed in a pure water non-solvent coagulation bath for phase transformation, removed and microwave-heated for 20-40 seconds, and then soaked and washed in deionized water to obtain a porous ion-conducting membrane.

2. The preparation method according to claim 1, characterized in that, In step S1: The mass ratio of the PVDF powder, the solvent dye, the organic pigment and the organic solvent is (15~25):(1~5):(1~5):(65~83).

3. The preparation method according to claim 1, characterized in that, In step S1: The organic solvent is any one of N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide, and N-methylpyrrolidone.

4. The preparation method according to claim 1, characterized in that, In step S1: The organic pigment is in granular form with a particle size of 0.5~2μm.

5. The preparation method according to claim 1, characterized in that, In step S1: The heating and stirring dissolution process is carried out at a temperature of 70°C, a rotation speed of 500~1000 r / min, and a time of 2~5 h. The vacuum degassing time is 24 hours; The film-forming solution is stored at room temperature and in an environment with an air humidity of less than 40% (RH).

6. The preparation method according to claim 1, characterized in that, In step S2: The thickness of the coating is 200~300μm; The temperature of the pure water non-solvent coagulation bath is 20~30℃; The settling time for the phase transformation is 5 to 20 minutes.

7. The preparation method according to claim 1, characterized in that, In step S2: The soaking and cleaning time is 60-120 minutes.

8. A porous ion-conducting membrane, characterized in that, It is prepared by the preparation method described in any one of claims 1 to 7.

9. The porous ion-conducting membrane according to claim 8, characterized in that, The porous ion-conducting membrane contains solvent dyes and organic pigments, and the uniformity of membrane modification is monitored by the chromophores contained in the solvent dyes and organic pigments.

10. An application of a porous ion-conducting membrane, characterized in that, The porous ion-conducting membrane prepared by the preparation method according to any one of claims 1 to 7, or the porous ion-conducting membrane according to any one of claims 8 to 9, is applied to an all-vanadium redox flow battery, wherein... The porous ion-conducting membrane has a coulombic efficiency of no less than 99.22% in the vanadium redox flow battery. The porous ion-conducting membrane has an energy efficiency of no less than 85.47% in the vanadium redox flow battery. The porous ion-conducting membrane retains no less than 99.46% of its capacity in the vanadium redox flow battery. The porous ion-conducting membrane achieves a coulombic efficiency of no less than 99.24% after 500 cycles in the vanadium redox flow battery. The porous ion-conducting membrane has an energy efficiency of no less than 85.08% after 500 cycles in the vanadium redox flow battery. The porous ion-conducting membrane retains no less than 94.32% of its capacity after 500 cycles in the vanadium redox flow battery.

Citation Information

Patent Citations

  • Lithium ion battery diaphragm and preparation method thereof

    CN113328204A

  • Modified diaphragm, and preparation method and application thereof

    CN113471627A

  • Preparation method of composite porous ion conduction membrane for all-vanadium redox flow battery

    CN118173845A

  • High-performance ion exchange membrane for flow battery and application of high-performance ion exchange membrane

    CN120300237A